KAJIAN YURIDIS PELAKSANAAN IZIN PERUBAHAN TANAH DARI LAHAN PERTANIAN KE NON PERTANIAN DI KABUPATEN KLATEN - DALIMAN, DALIMAN (Dinamika Hukum, 2015)
The purpose of this study wanted to examine the implementation of land use change permit from agriculture to non-agricultural land in the district of Klaten and knowing the obstacles and how to overcome these barriers. Background research, Klaten district several years shows the development progress quite rapidly, seen with the emergence of various public facilities, good service area which is knots activity or not. Based on the reference control approaches, it is necessary to realize an alternative policy, which is expected to solve the need for control over the land. The research method consists of this kind of research is normative or doctrinal nature descriptive study, the data used mainly secondary data including primary legal materials such as 1945, Law No. 5, 1960 regarding the Basic Regulation Agrarian Law No. 26 of 2007 on Spatial Planning, Law No. 32 of 2009 on the protection and management of the environment, the Act No. 41 of 2009 on the protection of agricultural land sustainable food., Government Regulation No. 16 of 2004 on land stewardship, Klaten District Regulation No. 11 of 2011 on Spatial Planning Klaten district in 2011-2031. In addition, journals, magazines, dictionaries, and the doctrine relevant to the object of research. The results showed that the implementation of land use change permit from agricultural to non-agricultural land in the district of Klaten in accordance with the laws and regulations that are used among the 1945 Constitution article 33, paragraph 3, of Law No. 5 of 1960 on the Basic Agrarian Law, Law No. .26 of 2007 on Spatial and Klaten District Regulation No.11 of 2011 on Spatial Planning. Caused every year there is a change of land use for drying paddy, this does not violate the provisions of the legislation. It also does not violate the provisions of the RTRW Klaten district, because compliance with zoning-zoning that has been set in the RTRW Klaten district. Keywords: execution permits the change of agricultural land to non-agricultural.